Native valve endocarditis complicated by abscess formation caused by Rothia mucilaginosa. (2021) - Haddad, S.; Saade, Y.; Ramlawi, B.; Kreidieh, B.; Gilbert, B.; Rao, S.
Abstract: Rothia mucilaginosa is increasingly recognized as an emerging pathogen associated with endocarditis. It has mostly been reported a causative agent for prosthetic valve endocarditis. The previously reported cases of native valve endocarditis caused by this organism only required medical treatment with no surgical intervention. We report a case of R. mucilaginosa native valve endocarditis complicated by abscess formation requiring surgical intervention and review the literature of native valve endocarditis caused by this organism.